2019
DOI: 10.1039/c8tb01491d
|View full text |Cite
|
Sign up to set email alerts
|

Micron-sized PFOB liquid core droplets stabilized with tailored-made perfluorinated surfactants as a new class of endovascular sono-sensitizers for focused ultrasound thermotherapy

Abstract: The effect of micro-droplet concentration on HIFU beam absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…This study confirmed the capabilities of PFOB-FTAC micron size droplets to enhance the local absorption of focused ultrasound, as already reported by Desgranges [57]. Differential metrics with and without injection of sonosensitizers showed a significant improvement in the temperature elevation achieved, inducing a dramatic amplification of the thermal dose in the target area.…”
Section: Enhancement Of Hifu Thermal Effect By Liquid-core Micron-sizsupporting
confidence: 90%
See 4 more Smart Citations
“…This study confirmed the capabilities of PFOB-FTAC micron size droplets to enhance the local absorption of focused ultrasound, as already reported by Desgranges [57]. Differential metrics with and without injection of sonosensitizers showed a significant improvement in the temperature elevation achieved, inducing a dramatic amplification of the thermal dose in the target area.…”
Section: Enhancement Of Hifu Thermal Effect By Liquid-core Micron-sizsupporting
confidence: 90%
“…F-TAC molecules consist of a fluorinated hydrophobic moiety exhibiting a high affinity for PFC droplets and a hydrophilic moiety made of a polyTRIS oligomer as illustrated in Figure 1(a). The surfactant was synthesized in one step by free radical polymerization as previously described [57]. The liquid-core PFOB-FTAC sonosensitizers were prepared using a Polytron homogenizer (model PT3100) from Kinematica (Luzern Switzerland).…”
Section: Sonosensitizersmentioning
confidence: 99%
See 3 more Smart Citations